Prevalence and associated factors of sugar-sweetened beverages intake among schoolchildren aged 9 to 17 years from bogotá, Colombia: The fuprecol study (2017)
Objective: The aim of the present study was to describe the intake of sugar-sweetened beverages and to examine of associated factors among schoolchildren from Bogota, Colombia. Methods: From a total of 8,136 schoolchildren and adolescents (age 9-17.9 years) taking part in the FUPRECOL Study. Sugar-sweetened beverages intake was based on intake from “regular soda”, “drink tea” and/or “concentrated juices”. Body weigth, heigth, body mass index (BMI), waist circumference, and percentage body fat by electrical bioimpedance analysis were measured such as adiposity markers. Associated factors (sex, age, abdominal obesity, BMI classification, mothers’ and fathers’ educational level and nutritional status by “Krece plus” questionnaire), were collected by structured questionnaire. Associations were established through a binary logistic regression. Results: Of the subjects, 58.4% were women. According to sex, boys response highest intake of “regular soda” daily/weekly frequency of the 70.9% and 21.0%, respectively, followed by “concentrated juices” (64.4% weekly vs. 11.3% daily). In both gender, the prevalence of abdominal obesity was higher in schoolchildren that responded to intake “regular soda” (23.3%), “concentrated juices” (13.2%) and “drink tea” daily (9.7%). Age [OR 1.15 (95%CI 1.03 to 1.28)], mothers’ [OR 1.30 (95%CI 1.03 to 1.65)], and fathers’ [OR 1.34 (95%CI 1.01 to 1.79) low educational level and nutritional status [OR 2.60 (95%CI 2.09 to 3.25)], were associated with daily intake of “regular soda”. Conclusion: Age, parental education level and dietary patterns were associated with sugar-sweetened beverages in schoolchildren in Bogota, Colombia. We recommended comprehensive interventions which are involved nutritional and educational component among children and adolescents from Bogota, Colombia. © 2017, Grupo Aula Medica S.A. All rights reserved.